2012
DOI: 10.1371/journal.pone.0050255
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Epidermis of the Neotropical Catfish Pimelodella lateristriga (Lichtenstein, 1823) with Emphasis in Club Cells

Abstract: The epidermis of Ostariophysi fish is composed of 4 main cell types: epidermal cells (or filament containing cells), mucous cells, granular cells and club cells. The morphological analysis of the epidermis of the catfish Pimelodella lateristriga revealed the presence of only two types of cells: epidermal and club cells. The latter were evident in the middle layer of the epidermis, being the largest cells within the epithelium. Few organelles were located in the perinuclear region, while the rest of the cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…We have here demonstrated that club cells are indeed present in high density in the skin of the jundiá, that these cells are large and rounded, and located in the middle of the stratified epithelium. Interestingly, club cells of R. quelen are binucleated, as has been found for other catfishes (e.g., Chapman & Johnson, 1997;Smith, 2000;Guerra et al, 2006;Damasceno et al, 2012) suggesting an intense cell metabolic activity; the significance of this finding, however, remains to be clarified.…”
Section: Concentration Of Skin Homogenatementioning
confidence: 55%
See 1 more Smart Citation
“…We have here demonstrated that club cells are indeed present in high density in the skin of the jundiá, that these cells are large and rounded, and located in the middle of the stratified epithelium. Interestingly, club cells of R. quelen are binucleated, as has been found for other catfishes (e.g., Chapman & Johnson, 1997;Smith, 2000;Guerra et al, 2006;Damasceno et al, 2012) suggesting an intense cell metabolic activity; the significance of this finding, however, remains to be clarified.…”
Section: Concentration Of Skin Homogenatementioning
confidence: 55%
“…In Characiformes, which features the largest number of species assessed in this context, alarm responses to alarm cells substances have been reported, for example, in Brycon amazonicus (Honda et al, 2008); Brycon cephalus (Ide et al, 2003); Gymnocharacinus bergi (Cordi et al, 2005); Leporinus macrocephalus (Alves et al, 2013); Leporinus piau ; Mimagoniates lateralis and M. microlepis (Duboc, 2007), and Piaractus mesopotamicus (Jordão & Volpato, 2000). In the Siluriformes, the second order most studied in this context, six species have been evaluated: Arius felis (e.g., Smith 2000), Clarias gariepinus (e.g., Guerra et al, 2006;van de Nieuwegiessen et al, 2008;van de Nieuwegiessen et al, 2009), Ictalurus punctatus (e.g., Chapman & Johnson, 1997;Valentic & Caprio, 1994), Pimelodella lateristriga (e.g., Damasceno et al, 2012), Pseudoplatystoma corruscans (e.g., Giaquinto & Volpato, 2001). However, only two studies were found about the role of epithelial alarm cells on behavioral responses in jundiá, R. quelen.…”
Section: Discussionmentioning
confidence: 99%
“…Mittal, Garg, and Verma () described the surface architecture of the skin of a catfish, Bagarius bagarius . More recently, Damasceno, Monteiro, Duboc, Dolder, and Mancini () examined the morphology of the epidermis, using scanning electron microscope, of the skin of Pimelodella lateristriga . Joshi, Bisht, and Agarwal () gave an account of different types of adaptive modifications, using scanning electron microscope, in the general body epidermis, snout, lip, adhesive apparatus and paired fin of Pseudochenei sulcatus .…”
Section: Introductionmentioning
confidence: 99%
“…The skin is self active secretory organ that their cellular components provide many useful products. Goblet cells secrete mucus that keep the body surfaces moist and protect it from stressors [2], club cells produce the alarm substances that initiate the alarm reaction [3] and melanocytes produce pigments to provide the fish with specific colorations [4]. The skin is also a vehicle for coetaneous sense organs that allowed the fish for detection of predators and foods.…”
Section: Introductionmentioning
confidence: 99%